(3fTQ GddWGFa aj bWQ GdWGFas - (3Ydj Hf eMeO Hf Ydj Hf YHO GdQMef GHf YQGb GdcfGfj, fhQ GdOjf,J (B963 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi Gdef hGddWGFa s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B218s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B534 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B279 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs